Q. 57

# Solve the followi

Given: to find:
Solution of the above quadratic equation.

Solution:

In factorization, we write the middle term of the quadratic equation either as a sum of two numbers or difference of two numbers such that the equation can be factorized.    ⇒ 3(9x2 + 1 – 6x) – 2(4x2 + 9 + 12x) = 5(6x2 – 3 + 7x)

⇒ 27x2 + 3 – 18x - 8x2 - 18 – 24x = 30x2 - 15 + 35x

⇒ 19x2 - 42x – 15 = 30x2 - 15 + 35x

⇒19x2 - 30x2 - 42x – 35x - 15 + 15 = 0

⇒ -11x2 - 77x = 0

⇒ 11x2 + 77x = 0

⇒ 11x(x + 7) = 0

⇒ x=0 and (x+7)=0

⇒ x=0 and x=-7

⇒ x = 0, - 7

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Introduction to Linear Equations in Two Variables62 mins  Pair of Linear Equations-Yahaan se laye marks57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 